Tissue Factor Structure and Function - Saulius Butenas (Scientifica)
Tissue factor (TF) is an integral membrane protein that is essential to life. It is a component of the factor VIIa-TF complex enzyme and plays a primary role in both normal hemostasis and thrombosis. With a vascular injury, TF becomes exposed to blood and binds plasma factor VIIa, and the resulting complex initiates a series of enzymatic reactions leading to clot formation and vascular sealing. Many cells, both healthy, and tumor cells, produce detectable amounts of TF, especially when they are stimulated by various agents. Despite the relative simplicity and small size of TF, there are numerous contradictory reports about the synthesis and presentation of TF on blood cells and circulation in normal blood either on microparticles or as a soluble protein. Another subject of controversy is related to the structure/function of TF. It has been almost commonly accepted that cell-surface-associated TF has low (if any) activity, that is, is “encrypted” and requires specific conditions/reagents to become active, that is, “decrypted.” However there is a lack of agreement related to the mechanism and processes leading to alterations in TF function. In this paper TF structure, presentation, and function, and controversies concerning these features are discussed.